Evaluation of edge-based interaction on a square smartwatch. Issue 109 (January 2018) - Ahn, Sunggeun; Lee, Jaeyeon; Park, Keunwoo; Lee, Geehyuk
Highlights: Exploration of edge-based interaction for a square smartwatch: single-edge, multiple-edge, and, edge x screen techniques. Evaluation of 1D and 2D pointing using square smartwatch edges in comparison with touchscreen-based pointing. Qualitative and quantitative empirical data for the design of edge x screen interaction. Discussion of design options of edge x screen interaction based on the empirical results. Abstract: Researchers are proposing many approaches to overcome the usability problem of a smartwatch owing to its small touchscreen. One of the promising approaches is to use touch-sensing edges to expand the control space of a smartwatch. We considered possible interaction techniques using touch-sensing edges in combination with the smartwatch touchscreen: single-edge, multi-edge, and edge  ×  screen (edge and touchscreen in combination). We call these techniques square watch interaction (SWI) techniques in this paper because they exploit the form factor of a square smartwatch. To explore the design space and evaluate the usability of the SWI techniques, we implemented a square smartwatch prototype with touch-sensitive edges, and conducted a series of user experiments. The experiment results showed that the SWI techniques enable precise 1D pointing and occlusion-free 2D pointing. The experiments also produced empirical data that reflect human manual skills for the edge  ×  screen techniques. The produced empirical data will provide a practical guideline for the application of the edge  ×  screen techniques.